“It’s Kinda Weird”: Hybrid Identities in the International Undergraduate Community - Adewale, Titilola; D'Amico, Mark M.; Salas, Spencer (Journal of International Students, 2018)
With benefits international students bring to campus, universities have adopted aggressive recruitment practices and increased institutional support for their retention and positive college engagement (Hegarty, 2014). Due to globalization, increasing numbers of international students enter college with multiple cultural/national affiliations (Gomes, Berry, Alzougool, & Chang, 2014). Yet, little is known about these complex identities and how they shape students’ experiences in U.S. higher education. Using Schlossberg’s Transition Theory, the article leverages interview data to theorize hybrid national/cultural identities of five “international” undergraduate students at a private university on the Eastern seaboard. Although the institution used passport information to categorize student nationality, participants chose to self-identify less categorically. Our discussion recommends dialogue around international students’ identity constructs to thoughtfully affirm hybridity.